NATIONAL REGULATORY REQUIREMENTS AND STANDARDIZED - XUDAYBERDIYEVA, Zarnigor (The Lingua Spectrum, 2025)
This article examines the alignment between national regulatory requirements and standardized competency frameworks in translator training. As translation becomes increasingly shaped by market demands, technological innovation, and quality assurance norms, the need for consistent, competence-based training models has become critical. The study analyzes major international frameworks – such as the PACTE model, the EMT competence framework, and ISO 17100 translation service standards – alongside national accreditation practices used in various higher-education systems. Through comparative analysis of scholarly literature and regulatory documents, the paper identifies key gaps between institutional curricula and market-driven competency expectations, particularly in technological, professional, and ethical domains. The findings suggest that the adoption of harmonized competency criteria, supported by regulatory guidelines and quality assurance mechanisms, can significantly improve translator preparedness and professionalization. Recommendations are provided for integrating standardized models into national translator-training policies to ensure consistent educational outcomes and alignment with global industry standards.